Identifying Continuous Quality Improvement Priorities in Maternal, Infant, and Early Childhood Home Visiting. Issue 2 (March 2016) - Preskitt, Julie; Fifolt, Matthew; Ginter, Peter M.; Rucks, Andrew; Wingate, Martha S.
Abstract : Objective: The purpose of this article was to describe a methodology to identify continuous quality improvement (CQI) priorities for one state's Maternal, Infant, and Early Childhood Home Visiting program from among the 40 required constructs associated with 6 program benchmarks. The authors discuss how the methodology provided consensus on system CQI quality measure priorities and describe variation among the 3 service delivery models used within the state. Design: Q-sort methodology was used by home visiting (HV) service delivery providers (home visitors) to prioritize HV quality measures for the overall state HV system as well as their service delivery model. Results: There was general consensus overall and among the service delivery models on CQI quality measure priorities, although some variation was observed. Measures associated with Maternal, Infant, and Early Childhood Home Visiting benchmark 1, Improved Maternal and Newborn Health, and benchmark 3, Improvement in School Readiness and Achievement, were the highest ranked. Conclusions: The Q-sort exercise allowed home visitors an opportunity to examine priorities within their service delivery model as well as for the overall First Teacher HV system. Participants engaged in meaningful discussions regarding how and why they selected specific quality measures and developed a greater awareness and understanding of a systems approach to HV within the state. The Q-sort methodology presented in this article can easily be replicated by other states to identify CQI priorities at the local and state levels and can be used effectively in states that use a single HV service delivery model or those that implement multiple evidence-based models for HV service delivery. Abstract : This article discusses consensus on continuous quality improvement (CQI) priorities for one state's Maternal, Infant, and Early Childhood Home Visiting program and describes variation among the 3 service delivery models used within the state.